Is certain food and nutrients associated with the risk of lung cancer? A systematic review - Wesołowska, Katarzyna; Kargul, Kinga; Pelczar, Magdalena; Puszka, Dorota; Dyczek, Maria; Kasprzak, Karolina; Poręba, Małgorzata; Krasoń-Orłowska, Ewa; Piasny, Marta; Lew, Katarzyna (Journal of Education, Health and Sport, 2024)
This review explores the intricate relationship between dietary factors and lung cancer risk based on a thorough examination of relevant literature and articles. The findings highlight a significant association between specific dietary elements and lung cancer risk. Increased intake of fiber, fruit, and vitamin C is linked to a notable 9% reduction in risk, particularly for squamous cell carcinoma. Notably, vegetables exhibit a risk reduction for current smokers, while offal, red meat, and processed meat may elevate risk, especially in heavy smokers. Contradictory evidence surrounds dairy products, with fermented dairy inversely correlated. Beer and cider consumption are associated with an increased risk, primarily among current smokers. In contrast, avocados demonstrate a promising link to decreased lung cancer risk. Vitamin K intake shows an inverse relationship, particularly in males and ever smokers. High retinol intake may elevate risk, potentially modifying the effects of tobacco exposure. Nuts consumption is significantly linked to reduced lung cancer risk and overall cancer mortality. Dietary polyunsaturated fatty acids (PUFA) demonstrate a noteworthy risk reduction for lung cancer, with supplementation improving overall survival in patients with the disease. Palmitic acid, a component of saturated fatty acids, is implicated in promoting lung metastasis, emphasizing the intricate nature of dietary influences on cancer. In summary, while lung cancer is primarily associated with tobacco smoking, this review underscores the multifaceted interplay between diet and lung cancer risk. Further research is crucial to unravel underlying mechanisms and provide definitive evidence on the impact of specific dietary factors, emphasizing the importance of continued exploration in this complex field.